Letter to the editor regarding "Carotid endarterectomy outcomes according to anesthesia method: General anesthesia or regional anesthesia" - Ayhan Muduroglu; Mustafa Selcuk Atasoy; Serdar Badem (Turkish Journal of Vascular Surgery)
[Turk J Vasc Surg 2024; 33(3.000): 189-90]